SISTEM INFOMASI ADMINISTARSI KEUNGAN SISWA BERBASIS WEB DI SEKOLAH MAHABODHI VIDYA - Purwanto; Mundirin -; Natalia Bani Pratiwi (Institut Sains dan Teknologi Al-Kamal, 2021)
The school payment system at the Mahabodhi Vidya School is still done manually both in term of transactions and data recap. Thus slowing down the payment process, recording and recap of payments. This causes the processes related to school payments have not run optimally. The overcome this problem, the authors propose to design and build applications that suport databases systems so that school payment processing is more effective and efficient. The application of financial administration information systems at the Mahabodhi Vidya School was designed using the waterfall development method with several stages, namely requirements analysis, system design, writing program code, testing programs, and maintaining programs. This application is designed using UML model visualization and developed using the PHP dan MySql programming language as a database. The conclusion of this study is that the Financial Statement Informatin System at Mahabodhi Vidya School has been completed. This systems has a feature so that payments can be made by installments and payment data can be seen in detail. Keywords: system information, payment of SPP, database, waterfall